Primary care clinical management following self-harm during the first wave of COVID-19 in the UK: population-based cohort study. Issue 2 (14th February 2022) - Steeg, Sarah; Carr, Matthew; Trefan, Laszlo; Ashcroft, Darren; Kapur, Navneet; Nielsen, Emma; McMillan, Brian; Webb, Roger
Abstract : Objectives: A substantial reduction in self-harm recorded in primary care occurred during the first wave of COVID-19 but effects on primary care management of self-harm are unknown. Our objectives were to examine the impact of COVID-19 on clinical management within 3 months of an episode of self-harm. Design: Retrospective cohort study. Setting: UK primary care. Participants: 4238 patients with an index episode of self-harm recorded in UK primary care during the COVID-19 first-wave period (10 March 2020–10 June 2020) compared with 48 739 patients in a prepandemic comparison period (10 March-10 June, 2010-2019). Outcome measures: Using data from the UK Clinical Practice Research Datalink, we compared cohorts of patients with an index self-harm episode recorded during the prepandemic period versus the COVID-19 first-wave period. Patients were followed up for 3 months to capture subsequent general practitioner (GP)/practice nurse consultation, referral to mental health services and psychotropic medication prescribing. We examined differences by gender, age group and Index of Multiple Deprivation quintile. Results: Likelihood of having at least one GP/practice nurse consultation was broadly similar (83.2% vs 80.3% in the COVID-19 cohort). The proportion of patients referred to mental health services in the COVID-19 cohort (4.2%) was around two-thirds of that in the prepandemic cohort (6.1%). Similar proportions were prescribed psychotropic medication within 3 months in the prepandemic (54.0%) and COVID-19 first-wave (54.9%) cohorts. Conclusions: Despite the challenges experienced by primary healthcare teams during the initial COVID-19 wave, prescribing and consultation patterns following self-harm were broadly similar to prepandemic levels. We found no evidence of widening of digital exclusion in terms of access to remote consultations. However, the reduced likelihood of referral to mental health services warrants attention. Accessible outpatient and community services for people who have self-harmed are required as the COVID-19 crisis recedes and the population faces new challenges to mental health.